Potential of Paitan (Tithonia diversifolia) and Cow Manure For Available Nutrients Supply On Sandy Beach Soil - Peniwiratri, Lelanti; Afany, Miseri Ruslan (RSF Conference Series: Engineering and Technology, 2022)
The primary macronutrients are required in large amounts for optimum plant growth. Sandy beach soil that is widely distributed, has a granular structure and is poor in primary macronutrients. Cow manure can improve the struktur of soil and Paitan (Tithonia diversifolia) can increase the availability of primary macro nutrients. This study aims to determine the effect of cow manure and Paitan (Tithonia diversifolia) on the nutrient availability of sand beach soil. The study used a completely randomized design (CRD) with 2 factors, the first factor was the dose of cow manure consisting of 3 levels 0; 2.5 and 5% of the weight of the soil. The second factor is the dose of Paitan (Thitonia diversifolia) which consists of 4 levels of 0; 2.5; 5 and 7.5%. of soil weight To determine the effect of treatment, variance analysis (ANOVA) was used and followed by a follow-up test using Duncan Multiple Range Test (DMRT) at a test level of 5%. The results showed that the application of cow manure and Paitan (Thitonia diversifolia) had a significant effect on increasing N available , P available and K available nutrients. The application of 5% cow manure and Paitan (Thitonia diversifolia) 5% has the potential to increase N available , P available and K available. sand beach soil is the highest